Ultrafast Racetrack Based on Compensated Co/Gd‐Based Synthetic Ferrimagnet with All‐Optical Switching. (26th October 2022) - Li, Pingzhi; Kools, Thomas J.; Koopmans, Bert; Lavrijsen, Reinoud
Abstract: Spin‐orbitronics and single pulse all‐optical switching (AOS) of magnetization are two major successes of the rapidly advancing field of nanomagnetism in recent years, with high potential for enabling novel, fast, and energy‐efficient memory and logic platforms. Fast current‐induced domain wall motion (CIDWM) and single shot AOS have been individually demonstrated in different ferrimagnetic alloys. However, the stringent requirement for their composition control makes these alloys challenging materials for wafer scale production. Here, fast CIDWM and energy efficient AOS in a synthetic ferrimagnetic system based on multilayered [Co/Gd]2 are simultaneously demonstrated. First, it is shown that AOS is present in its full composition range. It is found that current‐driven domain wall velocities over 2000 m s ‐1 at room temperature, achieved by compensating the total angular momentum through layer thickness tuning. Furthermore, analytical modeling of the CIDWM reveals that Joule heating needs to be treated transiently to properly describe the CIDWM for our sub‐ns current pulses. The studies establish [Co/Gd]‐based synthetic ferrimagnets to be a unique materials platform for domain wall devices with access to ultrafast single pulse AOS. Abstract : The results demonstrate a material platform capable of energy efficient all‐optical creation of magnetic domain and fast current driven coherent domain motion. Such system allows for bridging the two booming fields of solid‐state applications, i.e., the spintronics and the integrated photonics.